2017
DOI: 10.1007/s10758-017-9350-z
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Turkish as a Foreign Language with Interactive Whiteboards: A Case Study of Multilingual Learners

Abstract: This study attempts to explore the effects of interactive whiteboard (IWB) technology use on students' achievement and perceptions in Turkish as a foreign language instructional context. The participants included 19 Nigerian Turkish Language learners who were all fluent in three languages: English, Hausa, and their tribal languages. They had been learning Turkish for the last four months when they began the study using an IWB in their Turkish writing classes. For the 14-week study, participants were exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Previous studies reported multiple benefits of interactive whiteboard, such as increasing interactions [ 3 , 5 , 31 ], increasing learning engagement [ 1 , 25 ], enhancing learning efficiency [ 30 , 31 ], getting access to more resources [ 6 ], promoting learner-centered learning [ 25 ], involving tactile or kinesthetic learners [ 26 , 30 ], saving time for class preparation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported multiple benefits of interactive whiteboard, such as increasing interactions [ 3 , 5 , 31 ], increasing learning engagement [ 1 , 25 ], enhancing learning efficiency [ 30 , 31 ], getting access to more resources [ 6 ], promoting learner-centered learning [ 25 ], involving tactile or kinesthetic learners [ 26 , 30 ], saving time for class preparation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IWBs offer a time-saving advantage since they are essentially computers that can connect to the internet, allowing users to seamlessly access multimedia resources [ 27 , 30 , 31 ]. With a plethora of multimedia resources available, teachers can use existing materials on the board, thereby reducing the need for extensive material-preparation and lecturing [ 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are some studies focusing on case marker transference errors and suffixation problems of learners of Turkish as a foreign language in the literature. As Şengül and Türel (2017) asserted, studies mostly aimed to find out the most appropriate ways to teach Turkish language effectively to make students 'users' of the language rather than only 'learners'. Tunçel (2013) stated that the students learning Turkish as a foreign language are better to have a good command of Turkish language grammar for being good at expressing themselves successfully.…”
Section: Case Markersmentioning
confidence: 99%
“…Şengül and Türel (2017) used two main vanishing points to correct the textual images of perspective distortion. First of all, the parallel baselines in the text line and the blank information between the paragraphs were extracted, and then the positions of the horizontal vanishing point and the vertical vanishing point were estimated, respectively [5]. These two methods analyze the characters of the character itself in the text plane and calculate the single projection transformation matrix used for correction.…”
Section: Literature Reviewmentioning
confidence: 99%